Survival from Septic Shock Secondary to Disseminated Group A Streptococcal Infection after Central Extracorporeal Membrane Oxygenation - Asfari, A.; Ahmed, M.; Edwards, L. R.; Irby, K.; Agarwal, A.; Pasala, S.; Prodhan, P.; Frazier, B.; Sanders, R. C., Jr. (Journal of Child Science, 2017)
Objective The objective of this study was to describe a case of severe life-threatening acute respiratory distress syndrome (ARDS) and septic shock in a child who responded to a prolonged extracorporeal membrane oxygenation (ECMO) support course utilizing different cannulation techniques depending on the physiological derangement until he recovered.Design This is a case report.Setting This study was done at the medical–surgical pediatric intensive care unit in an academic freestanding children's hospital.Patient A previously healthy 4-year-old boy was presented with respiratory distress and fever. He was diagnosed with respiratory syncytial viral upper respiratory tract infection and group A β-hemolytic Streptococcus septic shock.Interventions The patient was referred to peripheral ECMO for hemodynamic, ventilatory, and oxygenation support; conversion to central ECMO to augment blood flow; and transition to extracorporeal carbon dioxide removal before successful wean off extracorporeal support.Measurements and Main Results Patient experienced severe pediatric ARDS and septic shock that were refractory to maximal medical therapy. Patient was able to be decannulated after 75 days of extracorporeal support. He was weaned completely off of mechanical ventilation and oxygen after 6 months. The only neurological deficit he exhibited was poor fine motor skills of his hands for which he continued to receive physical therapy.Conclusion Central ECMO may benefit children with pediatric ARDS and septic shock who require higher flows than what can be provided from peripheral ECMO. Extracorporeal membrane carbon dioxide removal may be an effective option in children who do not respond to mechanical ventilation alone.
Keywords: central extracorporeal membrane oxygenation; extracorporeal carbon dioxide removal; group A β-hemolytic Streptococcus; intensive care unit; outcomes; pediatric; septic shock